2015
DOI: 10.1021/acs.jmedchem.5b00553
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Neplanocin A Analogues as S-Adenosylhomocysteine Hydrolase Inhibitors and Their Antiviral and Antitumor Activities

Abstract: On the basis of the potent inhibitory activity of neplanocin A (1) against S-adenosylhomocysteine (AdoHcy) hydrolase, we analyzed the comprehensive structure-activity relationships by modifying the adenine and carbasugar moiety of 1 to find the pharmacophore in the active site of the enzyme. The introduction of 7-deazaadenine instead of adenine eliminated the inhibitory activity against the AdoHcy hydrolase, while 3-deazaadenine maintained the inhibitory activity of the enzyme, indicating that N-7 is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…In the present study, we identified two carbocyclic adenosine analogues, FHA and FHNA, as inhibitors of CHIKV and SFV replication. These compounds were originally designed as substrate analogue inhibitors of the host enzyme SAH hydrolase and were shown to inhibit this enzyme in vitro with 50% inhibitory concentration values of 0.37 and 0.91 M, respectively (31). In CPE reduction assays, FHA and FHNA strongly inhibited CHIKV with EC 50 values of 0.12 and 0.18 M, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we identified two carbocyclic adenosine analogues, FHA and FHNA, as inhibitors of CHIKV and SFV replication. These compounds were originally designed as substrate analogue inhibitors of the host enzyme SAH hydrolase and were shown to inhibit this enzyme in vitro with 50% inhibitory concentration values of 0.37 and 0.91 M, respectively (31). In CPE reduction assays, FHA and FHNA strongly inhibited CHIKV with EC 50 values of 0.12 and 0.18 M, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that FHNA resistance was not associated with increased resistance to the inhibitory effect of SAH or due to increased activity at low SAM concentrations. We then set out to investigate whether FHNA had a direct inhibitory effect on SFV nsP1, since we have also identified an FHNA analogue with a similar inhibitory activity against the host SAH hydrolase in vitro that is completely devoid of anti-CHIKV activity in cell-based assays (31). Previously, it was shown that halo-neplanocin A analogues inhibit SAH hydrolase via a mechanism that requires the NAD ϩ and the oxidation of the compound to a 3=-keto form (32).…”
Section: Discussionmentioning
confidence: 99%
“…37 FMCAP was synthesized using a known method in the literature 129,130 (Scheme 4), in which phenol was first treated with phosphorus oxychloride to generate phosphorylated phenyl dichlorophosphate 22, which was coupled with appropriate ester of L-alanine using triethyl amine in dichloromethane to give chlorophosphoramidate reagent (23,24). FMCA was then coupled with the appropriate chlorophosphoramidate reagent in tetrahydrofuran (THF) in basic condition using 1-methyl imidazole (NMI) to afford the phosphoramidate of FMCA (25,26) in good yield.…”
Section: Phosphoramidate Synthesis Of Fmcamentioning
confidence: 99%
“…Although the majority of these molecules are synthetic in origin, several carbocyclic nucleosides have been isolated from natural sources. Out of these naturally occurring compounds, aristeromycin and neplanocin A are interesting for having demonstrated antitumor and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Due to strong biological activities as well as interesting structural features, (amino)cyclopentitols attract attention of both biologists and organic chemists as potential therapeutics for the treatment of carbohydrate-metabolism-related disorders. Carbocyclic nucleosides such as neplanocin A (5), [13] aristeromycin (6) [14] and their numerous analogues [15][16][17][18][19] exhibit antiviral, antibacterial and antitumor activity. Carbocyclic nucleosides such as neplanocin A (5), [13] aristeromycin (6) [14] and their numerous analogues [15][16][17][18][19] exhibit antiviral, antibacterial and antitumor activity.…”
Section: Introductionmentioning
confidence: 99%